Pengaruh Brand Equity Terhadap Brand Loyalty Dimediasi oleh Customer Satisfaction pada Produk Avoskin Beauty di Tangerang - Meylinda, Rossa Rinte; Septyanto, Dihin (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to explore and provide empirical evidence not only regarding the relationship between Brand Equity and Customer Satisfaction, but also the role played by Customer Satisfaction as a mediator for Brand Loyalty. In addition to confirming a significant dimension based on Brand Equity for the Avoskin Beauty skincare product segment in Indonesia, especially in the Tangerang area. To achieve the research objectives, data collection techniques were collected through online questionnaires with 270 participants as respondents who had used and purchased at least 2 times the product under study and are domiciled in Tangerang. In analyzing the data, the researcher used a data analysis technique, namely partial least squares structural equation structural equation modeling. From the research conducted, the results show that for the skincare segment six of the eight proposed hypotheses are significantly related and can be accepted, especially customer satisfaction fully mediates perceived quality and brand trust on brand loyalty. Meanwhile, brand identification and lifestyle suitability cannot affect brand loyalty. These findings contribute that marketing must be carried out more effectively and sensitively to strategic developments in the business sector, especially in increasing product innovation in the skincare sector to create positive customer emotions and customer satisfaction in purchasing products in the future. It is hoped that this research will provide an understanding of business in the skincare sector and for further research, researchers can expand the demographics of research locations in Indonesia.